Decision-Making Responsibility: Development and Initial Validation of a New Measure for Low-Income, Nonresident Fathers. (January 2018) - Fagan, Jay; Dyer, Justin; Kaufman, Rebecca; Pearson, Jessica
Most measures of father involvement with children have been developed for use with middle-class fathers who reside with their children. The current study documents the development and initial validation of a new measure of decision-making responsibility for low-income fathers with a nonresident child. Focus groups conducted with 71 fathers revealed two dimensions of decision-making responsibility: making decisions with respect to direct care of the child and making decisions with respect to resources. Surveys were then collected from 542 nonresident fathers to validate a set of items measuring these two dimensions. The results of exploratory factor analysis and confirmatory factor analysis supported these factors. However, the results of convergent and predictive validity tests suggest that the resources factor does not add additional explanatory power above its association with the care factor. We suggest using only the seven care decision-making items in future studies.